Epidermal features of the floating leaves of Quereuxia angulata (Newberry) Krištofovič, an aquatic angiosperm from the Upper Cretaceous of Northeast China. (September 2021) - Liang, Fei; Tian, Ning; Sun, Wei; Wu, Qi; Liu, Bingcai; Wang, Hongshan
Abstract: Quereuxia angulata (Newberry) Krištofovič 1953, an aquatic herbaceous angiosperm with heterophyllous leaves, is a common element of the Late Cretaceous and Paleocene floras in the Northern Hemisphere. The floating leaves are rosulate and compound with many obovate leaflets while the submerged leaves are usually filiform and dichotomously branched. The leaves of Quereuxia are taxonomically difficult to delineate if only based on their gross morphology. Therefore, acquiring their anatomical information of the leaf epidermis is an important line of evidence for the natural classification of this fossil genus. In this report, we examine the epidermal features of well-preserved floating leaves of Q. angulata, collected from the Upper Cretaceous Yong'ancun Formation in Jiayin County, Heilongjiang Province, Northeast China. The leaves are hyperstomatic with brachyparacytic stomata. Both the adaxial and abaxial epidermal cells are usually irregularly pentagonal or hexagonal and sometimes isodiametric in shape. This is the first time that the epidermal features are examined for Quereuxia . The results provide valuable morphological characters in identifying the different species of this extinct genus. Highlights: Leaf epidermal features of the floating leaves of Quereuxia were first reported. Brachyparacytic stomata of Q. angulata leaves is different from those of the leaves of Trapaceae and Lythraceae. Leaf features further support the presence of seasonal or temporary drought in this area at during the Late Cretaceous.